Effect of Qris Use on MSME Business Income - Fatmawati, Fatmawati; Mutmainnah, Mutmainnah; Ponto, Sahrul (Advances in Economics & Financial Studies, 2024)
Purpose: This study aims to evaluate the effect of QRIS usage on business income for MSMEs in Jayapura City. Research Design and Methodology: The study used quantitative methods with simple linear regression analysis. Data was collected through questionnaires from MSME players who use QRIS in Jayapura City. The independent variable is the use of QRIS, while the dependent variable is business income. Findings and Discussion: The results of the analysis show that the use of QRIS has a significant positive effect on business income, with a regression coefficient of 1.017 and a p-value of 0.0000. This finding supports the hypothesis that the adoption of digital payment technology such as QRIS can increase business income. In addition, these results are in line with previous research showing the benefits of QRIS in improving operational efficiency and customer satisfaction. Implications: This research makes an important contribution to science and business practice, showing that QRIS can be an effective tool to improve the business performance of MSMEs in Indonesia. The findings encourage businesses to adopt QRIS to improve efficiency and profitability. However, this study is limited to a sample in Jayapura City and uses quantitative methods. Further research is recommended to explore the impact of QRIS in different regions and business sectors and consider a qualitative approach to gain deeper insights.